HIF1α-Dependent Induction of TFRC by a Combination of Intestinal Inflammation and Systemic Iron Deficiency in Inflammatory Bowel Disease - Fagundes, Raphael R.; Bourgonje, Arno R.; Hu, Shixian; Barbieri, Ruggero; Jansen, Bernadien H.; Sinnema, Nienke; Blokzijl, Tjasso; Taylor, Cormac T.; Weersma, Rinse K.; Faber, Klaas Nico; Dijkstra, Gerard (Frontiers in Physiology, 2022)
Background & Aims: Iron deficiency (ID) is a frequent extra-intestinal manifestation in patients with Inflammatory Bowel Disease (IBD), who often do not respond to iron supplementation. Iron is a cofactor for hydroxylases that suppress the hypoxia-inducible factor-1α (HIF1α), a transcription factor regulating iron homeostasis. We hypothesized that iron deficiency affects mucosal HIF1α activity in IBD. Methods: IBD patients (n=101) were subdivided based on iron status (ferritin levels or transferrin saturation) and systemic inflammation (C-reactive protein levels). 154 corresponding ileal and colonic biopsies were analyzed for differential expression of 20 HIF1α pathway-associated genes and related to iron and inflammation status. In vitro expression of selected HIF1α pathway genes were analyzed in wild-type and HIF1A-null Caco-2 cells. Results: Gene expression of the mucosal HIF1α pathway was most affected by intestinal location and inflammatory status. Especially, ileal mucosal TFRC expression, encoding the transferrin receptor TFR1, was increased in inflamed tissue (P<0.001), and further enhanced in ID. Accordingly, TFRC expression in inflamed tissue associated negatively with serum iron levels, which was not observed in the non-inflamed mucosa. The HIF1α pathway agonist DMOG increased TFRC expression in Caco-2 cells, which was blunted in HIF1A-null cells. Conclusions: We demonstrate that inflammation and anatomical location primarily determine HIF1α pathway activation and downstream TFRC expression in the intestinal mucosa. IBD patients with ID may benefit from treatment with HIF1α-agonists by 1) increasing TFRC-mediated iron absorption in non-inflamed tissue and 2) decreasing mucosal inflammation, thereby improving their responsiveness to oral iron supplementation.